Criteria to define rare diseases and orphan drugs: a systematic review protocol - Katie Kerr; Ghada Mohammed Abozaid; Amy McKnight; Hussain A Al-Omar (BMJ Open)
Introduction Rare diseases (RDs) are often chronic and progressive life-threatening medical conditions that affect a low percentage of the population compared with other diseases. These conditions can be treated with medications known as orphan drugs (ODs). Unfortunately, there is no universal definition of RDs or ODs. This systematic review (SR) will identify the quantitative and qualitative criteria and the underlying rationale used internationally to define RDs and ODs.Methods and analysis This protocol follows the conventions for the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (2015 guidelines). A SR will be conducted, including a search of the following databases: PubMed, MEDLINE, EMBASE, Scopus, Web of Science, GreyLit and OpenGrey. Eligible publications will be selected based on predetermined inclusion criteria. Extracted data will be analysed using thematic and content analyses of qualitative descriptors, whereas quantitative data will be analysed descriptively and reported in the form of frequencies and percentages.Ethics and dissemination No ethical approval is required since this SR focuses on the secondary analysis of data retrieved from the scientific literature. The outcomes of this SR will be published as part of a PhD thesis, presented at conferences, and published in peer-reviewed journals.PROSPERO registration number CRD42021252701.